Origin of 90° domain wall pinning in Pb(Zr0.2Ti0.8)O3 heteroepitaxial thin films - Su, Dong; Meng, Qingping; Vaz, Carlos A. F.; Han, Myung-Geun; Segal, Y.; Walker, Fred; Sawicki, Monica; Broadbridge, Christine; Ahn, Chong H. (Applied Physics Letters, 2011)
We describe a transmission-electron-microscopy study of the ferroelectric domains in an epitaxial Pb(Zr0.2Ti0.8)O3 (PZT) film grown on La0.7Sr0.3MnO3/SrTiO 3(001). We directly observe the pinning of 90 domain walls by pairs of misfit dislocations, respectively, with Burgers vectors a [100] and a [001]. Model calculations based on the elastic theory confirm our finding that, in addition to the depolarization field surrounding the dislocation, the strain field of misfit dislocation-pairs plays the primary role in the formation and pinning of a domains. © 2011 American Institute of Physics.
48 citations (Crossref) [2023-10-31] Citation Key Alias: pop00042 tex.type: [object Object]
Keywords: Depolarization fields; Domain walls; Domain-wall pinning; Elastic theory; Epitaxial growth; Ferroelectric domains; Ferroelectricity; Heteroepitaxial thin films; Heterojunctions; Lanthanum compounds; Lead; Manganese oxide; Model calculations; PZT; Strain fields; Zirconium; dept.phy